A Mixture of Ginkgo biloba L. Leaf and Hericium erinaceus (Bull.) Pers. Fruit Extract Attenuates Scopolamine-Induced Memory Impairments in Mice. (27th January 2022) - Hong, Seong Min; Yoon, Da Hye; Lee, Mi Kyeong; Lee, Jae Kang; Kim, Sun Yeou
Abstract : Alzheimer's disease (AD) is a neurodegenerative disease that is characterized by loss of memory and cognitive impairment via dysfunction of the cholinergic nervous system. In cholinergic dysfunction, it is well known that impaired cAMP response element-binding protein (CREB) and brain-derived neurotrophic factor (BDNF) signaling are major pathological markers and are some of the strategies for the development of AD therapy. Therefore, this study is aimed at evaluating whether a mixture comprising Ginkgo biloba L . leaf (GL) and Hericium erinaceus (Bull.) Pers . (HE) fruit extract (GH mixture) alleviated cognitive impairment induced in a scopolamine-induced model. It was discovered that GH reduced neuronal apoptosis and promoted neuronal survival by activating BDNF signaling in an in vitro assay. In addition, the GH ( p.o. 240 mg/kg) oral administration group significantly restored the cognitive deficits of the scopolamine-induced mouse group ( i.p. 1.2 mg/kg) in the behavior tests such as Y-maze and novel object recognition task (NORT) tests. This mixture also considerably enhanced cholinergic system function in the mouse brain. Furthermore, GH markedly upregulated the expressed levels of extracellular signal-regulated kinase (ERK), CREB, and BDNF protein levels. These results demonstrated that GH strongly exerted a neuroprotective effect on the scopolamine-induced mouse model, suggesting that an optimized mixture of GL and HE could be used as a good material for developing functional foods to aid in the prevention of neurodegenerative diseases, including AD.